Mouse Lemurs in an Assemblage of Cheirogaleid Primates in Menabe Central, Western Madagascar – Three Reasons to Coexist - Schäffler, Livia; Kappeler, Peter M.; Halley, John M. (Frontiers in Ecology and Evolution, 2021)
Ecological communities are structured by interactions between coexisting species that mutually influence their distribution and abundance. Ecologically similar species are expected to exclude one another from suitable habitat, so the coexistence of two mouse lemur species in an assemblage of several closely related cheirogaleid primates in the central Menabe region of Madagascar requires explanation. We assessed the occurrence of Madame Berthe’s mouse lemurs (Microcebus berthae) and Gray mouse lemurs (Microcebus murinus), and of two larger cheirogaleids, Coquerel’s giant mouse lemur (Mirza coquereli) and the western fat-tailed dwarf lemur (Cheirogaleus medius), by nocturnal line transect walks between 2003 and 2007. We explored interspecific interactions for four different scenarios with varying resource availability (degraded and non-degraded habitat in the wet and dry season), both on the regional spatial scale and on a finer local (transect) scale. We tested whether the interspecific distribution of mouse lemur individuals indicates interspecific competition and whether their regional coexistence might be stabilized by interactions with M. coquereli or C. medius. We developed the “Inter-Species Index of Attraction” (ISIA) to quantify the observed interspecific interactions within transects and determined if these were significantly different from a null model generated by a combination of randomization and bootstrapping to control for intraspecific aggregation. For the two mouse lemurs, interspecific spatial exclusion was most pronounced during the resource-poor dry season, consistent with the hypothesis of feeding competition. Seasonally varying distribution patterns indicated resource tracking in a spatio-temporally heterogeneous environment. The interspecific distribution of individuals suggested that the larger cheirogaleids benefit M. berthae at the expense of the more abundant M. murinus: spatial associations of both, M. coquereli and C. medius, with M. murinus were negative in most scenarios and across spatial scales, but neutral or even positive with M. berthae. Thus, our study revealed that coexistence among ecologically similar heterospecifics can rely on complex density-mediated interspecific processes varying with habitat quality and season. With regard to the stability of animal assemblages, this insight has major implications for biodiversity conservation.